2021
DOI: 10.1016/j.ceramint.2020.08.122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physical, optical, mechanical, and radiation attenuation properties of TiO2–Na2O–Bi2O3–B2O3 glasses

Abstract: A series of bismo-borate (50-x)B 2 O 3 -xTiO 2 -15Na 2 O-30Bi 2 O 3 glass samples (where x = 0, 2.5, 5, 7.5, and 10 wt %) doped with TiO 2 were fabricated via the melt-quenching technique. The gamma and neutron shielding, physical, optical, and mechanical properties of the prepared samples were investigated. The experimental results were measured using an HPGe detector. 152 Eu, 133 Ba, 137 Cs, and 60 Co radioactive sources were used with energies in the range of 81-1408 keV. The experimental results were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 41 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Accordingly, the increase in the use of hybrid material fills the interstitial spaces, thereby leading to more compactness and densification of the bandage formed during the coating process. 29 Therefore, it can be concluded that with an increase in the thickness of the material, there would be an increment in the density and thus leading to more attenuation characteristics in the developed material. Although, there can be a reduction in the flexibility aspects of the developed shielding bandage if more coated material and layers are used.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the increase in the use of hybrid material fills the interstitial spaces, thereby leading to more compactness and densification of the bandage formed during the coating process. 29 Therefore, it can be concluded that with an increase in the thickness of the material, there would be an increment in the density and thus leading to more attenuation characteristics in the developed material. Although, there can be a reduction in the flexibility aspects of the developed shielding bandage if more coated material and layers are used.…”
Section: Resultsmentioning
confidence: 99%
“…Following the determination of the linear attenuation coefficients (µ), many additional gamma radiation attenuation parameters were determined. To begin, we calculated the mass attenuation coefficients (µ) of the AL glasses using Equation (1) [26],…”
Section: Investigated Nuclear Shielding Parametersmentioning
confidence: 99%
“…To clarify the validity of the previous conclusions, the density was measured for each sample, and then plotted in Figure (3) for comparison, where the density is very sensitive to any changes that may occur in the internal structural of a solid material. The Vickers micro-hardness values HV were calculated for all studied samples, before and after the plasma treatment, according to the previous standard formula [22][23][24][25]; where F is the indentation load and d is the diagonal length impression, as seen in figure ( 4). It's clear that the incorporation of La-impurities acted to increase the glass hardness (resistance to elastic deformations) as a result to the strength of the atomic bonds in the glass structure induced by dopants [26][27][28][29].…”
Section: Structural Characterization and Phase Identificationmentioning
confidence: 99%